2016
DOI: 10.1097/pec.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

EMS Activations for School-Aged Children From Public Buildings, Places of Recreation or Sport, and Health Care Facilities in Pennsylvania

Abstract: Our identification of common EMS dispatch complaints, mechanisms of injury, and primary assessments can be used in the education of staff and preparation of facilities for medical emergencies and injuries where children spend time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…1,2,11 Psychiatric and behavioral emergencies were not listed in any previous survey data but were recently identified as the most common identifiable complaint requiring EMS activation from a health care facility in schoolaged children. 12 This is supported by our data because patients in our study were 57% female and ranged in age from 6 to 17 years (average 14 years). Our results also support an AAP publication whose authors describe the significant increase in mental health complaints made by pediatric patients in both emergency department and primary care settings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1,2,11 Psychiatric and behavioral emergencies were not listed in any previous survey data but were recently identified as the most common identifiable complaint requiring EMS activation from a health care facility in schoolaged children. 12 This is supported by our data because patients in our study were 57% female and ranged in age from 6 to 17 years (average 14 years). Our results also support an AAP publication whose authors describe the significant increase in mental health complaints made by pediatric patients in both emergency department and primary care settings.…”
Section: Discussionsupporting
confidence: 86%
“…11 The authors of the other study evaluated all EMS encounters for school-aged children (age ≥5 years) from public locations (including a subgroup of patients from medical facilities) but did not identify types of medical facilties. 12 The authors of both of these studies used aggregated EMS data that were neither validated through manual review nor confirmed with other data sources.…”
mentioning
confidence: 99%
“…This study included pediatric and adult patients, which contrasts with previous literature that has focused solely on the pediatric population [ 12 ] or was not specific to sport-related injuries [ 11 , 15 , 22 , 23 ]. Over two-thirds of EMS activations were for adults.…”
Section: Discussionmentioning
confidence: 99%
“…An EMS activation is when an EMS response is initiated when an individual calls 9-1-1. Among children, 11-22% of EMS activations originate from places of recreation or sport [ 11 , 12 ]. One study specifically examined pediatric EMS activations to places of recreation and sport using data collected by EMS agencies [ 12 ]; however, only location criteria were used to identify sports-related injuries while mechanism or cause of injury was not considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation